2019
DOI: 10.1249/mss.0000000000002214
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Cardiometabolic Risk Factor Clustering in Young Adults with Obesity

Abstract: Introduction There is a paucity of information on the clustering of cardiometabolic risk factors in young adults and how this clustering may vary based on whether or not they perform sufficient levels of physical activity. Methods We analyzed baseline data from 346 young adults (23.3 ± 4.4 yr) participating in the Healthy Body Healthy U clinical trial from 2015 to 2018. Cardiometabolic risk factors were measured according to standard procedures and mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 35 publications
2
14
0
1
Order By: Relevance
“…Physical activity provides numerous benefits for obese subjects. Together with diet, exercises play an important role in the primary prevention and management of excessive body weight 6 9 mostly due to favourable impact on body composition, prevention of obesity-related diseases and improve cardiometabolic parameters 10 12 . Therefore, the American College of Sports Medicine 13 , 14 , the European College of Sport Science 15 and the American Heart Association 8 recommend a minimum of 30 min of moderate-intensity endurance training five days per week or a minimum of 20 min of vigorous endurance activity three days per week.…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity provides numerous benefits for obese subjects. Together with diet, exercises play an important role in the primary prevention and management of excessive body weight 6 9 mostly due to favourable impact on body composition, prevention of obesity-related diseases and improve cardiometabolic parameters 10 12 . Therefore, the American College of Sports Medicine 13 , 14 , the European College of Sport Science 15 and the American Heart Association 8 recommend a minimum of 30 min of moderate-intensity endurance training five days per week or a minimum of 20 min of vigorous endurance activity three days per week.…”
Section: Introductionmentioning
confidence: 99%
“…Greater abdominal or trunk adiposity in young adults results in greater risk of cardiometabolic risk in later adulthood [8,9]. Healthy behaviors, such as physical activity [10] and a healthy overall diet, can decrease the risk of cardiometabolic disorders. The healthiness of the diet or diet quality may provide a better predictor of disease risk [11] than specific nutrients [12] or restricted food patterns [13].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of individual or combination of cardiometabolic risk factors has been termed 'cardiometabolic dysregulation' (CMD) or 'cardiometabolic risk' in the literature; a composite CMD score has been conveniently calculated as the simple count of cardiometabolic biomarkers in the respective high-risk ranges according to clinical criteria, which has the potential to be applied to different populations and would allow comparison across different studies. [31][32][33] Similar to AL, increased CMD was associated with stressful and traumatic life experiences, 34 cognitive decline, 32 and HRBs. 31 33 Shi et al 31 demonstrated that more healthy lifestyle behaviours, including abstinence from smoking, regular exercise, sufficient fruit and vegetable intake, less meat intake, modest alcohol intake and less television viewing time, were associated with reduced CMD among two generations of adults in the USA and Canada.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 80%
“…[31][32][33] Similar to AL, increased CMD was associated with stressful and traumatic life experiences, 34 cognitive decline, 32 and HRBs. 31 33 Shi et al 31 demonstrated that more healthy lifestyle behaviours, including abstinence from smoking, regular exercise, sufficient fruit and vegetable intake, less meat intake, modest alcohol intake and less television viewing time, were associated with reduced CMD among two generations of adults in the USA and Canada. However, no study has yet examined the relationship between CMD and various HRBs among the younger healthy Asian adult population.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 80%